Mortuary management and public health - Jaffar Hussain , A P; Khaja Mohiddin, Shaik (Journal of Indian Academy of Forensic Medicine, 2021)
Mortuary is the place where autopsy of human beings where death due to unnatural circumstances is conducted. An attempt has been made by the investigators to conduct a study related to the standards of present mortuaries and to address the requirement for future challenges. A total of 16 autopsy centres were selected for the study during the period 2018-2019. This study is based on the available information provided from different mortuaries. Three teaching hospitals, five area hospitals and eight rural hospitals were selected. Post-mortem examination in Telangana state are done in designated hospitals run by the Government only. Teaching hospital mortuaries are provided with relatively good facilities like sanitation, permanent water supply, waste disposal and incineration plants as compared to area hospitals and rural hospitals. Menace of rodents is seen in all mortuaries present in teaching hospitals, area hospitals and rural hospitals. Addiction to alcohol is frequently seen among mortuary workers and even among the doctors. Number of post-mortem examinations in teaching hospitals is higher compared to area and rural hospitals. There are several areas in mortuaries, which are prone to producing infections and foul smells. As the bodies start decomposing, the foul smell increases and hence bacteria are also abundant in these areas. Extensive biological waste is produced. Maggots and other insects, all add to the poor conditions within mortuaries. All together the atmosphere in and around mortuary is poor and renovation of mortuaries is the need of the day.